The variation in the frequency of surface air pressure systems on Iraq - Adnan Faleh, M’athir; Jabr WaSmi, Hussein (Al-Adab Journal, 2020)
The apparent movement of the sun to the north and south of the equator during the year, has a significant impact in the movement of the main and secondary pressure ranges to the north or south of their positions, and by virtue of Iraq’s position on the edge of the northern subtropical high pressure, it is greatly affected by this movement, and this makes it affected by different types of low and high pressure systems but unevenly, some continue to affect for months such as low in land seasonal Some of them are limited to a few hours or days, such as the Sudanese depression and the low Mediterranean sea, and some continue to affect for weeks such as the Siberian and European highlands and each type of these systems is characterized by weather conditions different from the other system, but it is rare to find similar climatic conditions within the same system. In order to clarify the impact of these surface pressure systems, the separation (20) meters between the contour lines was chosen because this interval gives a clear picture of the pressure systems, which will be addressed in this chapter through the analysis of the daily surface weather maps of the pressure level of 1000 mb